Tahap kepuasan pekerja terhadap prestasi persekitaran fizikal dalaman pejabat - Hashim, Abd. Jalil (2010)
The purpose of this study is to evaluate the satisfactory level of office staff on the performance of internal physical office environment. A literature study shows that there are many physical and non-physical factors that affect the satisfactory level of office workers. However, not all factors are taking into account as the focus of this study is on physical aspects in general such as temperature, natural lighting, electrical lighting, indoor air quality, sound, office space, working space, ergonomic and aesthetic. The method of performance measurement used in this study is based on Post-Occupancy Evaluation (POE). This method is divided into three levels including indicative, investigative and diagnostic. The writer has select workers from the government office building of Wisma Persekutuan as respondents for this study. From 100 questionnaires distributed only 87 have returned. Analysis has been done by using SPSS program and data are processed by using frequency, mean and Mann-Whitney U analysis. A result from frequency and mean analysis shows that majority of respondents have agreed that those nine factors have affected their performance in the office. Another result from the same analysis shows that not all respondents are satisfied with their office environment. The Mann-Whitney U analysis used to study whether the opinion is vary between gander and grade of service shows that male respondents are more satisfied with the internal physical office environment in comparing with female respondents, and the staff from professional grade of service are more satisfied in comparing with staff from support services.